KEBIJAKAN INDONESIA BELUM MENGAKUI KEMERDEKAAN KOSOVO PADA TAHUN 2008 - Mauliani, Ressy; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this research is to understand Indonesia Foreign Policy Has Not Admitted Kosovo Independence In 2008. Kosovo is a province in Serbia, but due to the uprising finally Kosovo secede from Serbia and stands today as a nation that also require confessions from other countries. Most countries chose to recognized and ignore the Kosovo Independence. Differently, Indonesia chose to did not recognize Kosovo Independence in 2008. Thus researcher question is Why Indonesia Foreign Policy Has Not Admitted Kosovo Independence In 2008.This research theoretically has built with Realism perspectives on International Relations and supported by Foreign Politic theory James N. Rossenau. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that Indonesia actually put themselve in the position of